Encyclopedia of communities of practice in information and knowledge management - Coakes, Elayne; Clarke, Steve (Hershey, PA : Idea Group Reference, 2006)
"This encyclopedia will give readers insight on how other organizations have tackled the necessary means of sharing knowledge across communities and functions"--Provided by publisher.
Includes bibliographical references and indexes.
Keywords: Organizational learning; Communities of practice; Knowledge management; Social networks; Social learning; Information society